Nocturnal pain in adhesive capsulitis and subacromial ımpingement syndrome - YAĞCI, İLKER (My University, 2023)
Background:Subacromial impingement syndrome (SIS) and adhesive capsulitis (AC) are the most common causes of shoulder pain. It is known that patients with both disorders have impaired sleep quality and increased levels of anxiety and depression. This study aimed to compare the sleep, disability, and affective states of patients with untreated AC and SIS.Method:Patients with shoulder pain for more than three months and diagnoses of AC and SIS were included in the study. Pain was assessed by visual analog scale (VAS), disability by shoulder pain and disability index (SPADI), sleep quality by Pittsburgh sleep quality index (PSQI), and anxiety and depression by hospital anxiety and depression scale (HADS).Results:The study included 65 patients (n=24 AC, n=41 SIS. Sleep was affected in both of the groups. The patients with AC had worse scores than patients with SIS including SPADI pain, SPADI-total, sleep latency, sleep duration, sleep disturbance, using sleep mediation (p<0.05). Sleep problems were correlated to anxiety and depression.Conclusions:Despite the patients with SIS had higher SPADI-pain levels, the patients with AC had higher scores of SPADI-disabilities. Both of the groups had nocturnal pain and sleep problems but patients with AC had higher amount of sleep problems and depression mood compared to patients with SIS.Keywords:Sleep problems, Shoulder pain, SIS, AC
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Sleep problems; Shoulder pain; SIS; AC